ORAL COLLAGEN AND AGING - Karunisa Kirana (Healthy Tadulako Journal (Jurnal Kesehatan Tadulako), 2023)
ABSTRACT Background and Objective: Skin is a barrier that protects the body from the outer environtment and has a cosmetic function. Aging is biological process that marked by deterioration of physiological function of the body. Collagen has responsible in stability and strength of body tissues. In recent years, oral collagen supplementation has become popular because it’s distributed to peoples as an anti aging therapy. The aim of this study is investigating that there is effect of oral collagen in order to prevent aging. Methods: I reviewed studies about oral collagen and aging. Studies were published within five years priors to 2020. I searched studies about them using keywords including aging, anti aging, oral collagen, and collagen. Conclusion: Oral collagen plays an important role in order to prevent aging. It can be absorbed effectively because the most form of oral collagen is hydrolyzed collagen, so our body doesn’t need to change it to a smaller molecule before use it. Oral collagen also doesn’t have side effects to our body. Therefore, it can be used to prevent aging together with controlling of intrinsic and extrinsic factors that contributing in skin aging. Keywords: aging, oral collagen, collagen.